Fusion of MxIRT1 Vesicles and Plasma Membrane is a Key Regulation Step of High Affinity Iron Transport in Response to Iron Supplement in Transgenic Yeast - Wang, Li-Yong; Feng, Bing; Li, Peng; Yang, Guang; Yin, Li-Ping (Asian Journal of Chemistry, 2012)
In previous study, it was found that heterologous expression of MxIRT1, one of iron-regulated transporters, sorted from endoplasmic reticulum (ER) to plasma membrane (PM) via vesicles trafficking in transgenic Saccharomyces cerevisiae. The sorting process was affected by surrounding iron existence. To clarify the detailed molecular mechanism in cells underlying vesicles trafficking responses to iron supplement, gene expression patterns and genetic networks in MxIRT1-transformed DEY1453 (fet3fet4) mutant strain were examined using global-scale microarrays and computational gene expressional analysis tools. The results showed that MxIRT1 transport may be involved in oxygen-dependent reactions, stress signal and membrane vesicles transport etc. Based on microarray data, the analyses focused on iron high affinity pathway including vesicle trafficking and membrane fusion. It was remarkably revealed that the expression of MxIRT1 made iron transport system work and most of MxIRT1-vesicles were transmitted toward plasma membrane and docked inside of plasma membrane but without fusion in the absence of iron. However, as supplying iron to the environment, the fusion of MxIRT1-vesicle with plasma membrane was promoted, which was just consistent with results from laser scanning confocal microscope observation. Therefore, it is concluded that MxIRT1 might function in place of FET3/FTR1 complex in yeast, and then induce the iron high affinity pathway from ER to plasma membrane via vesicles trafficking in lack of iron. Furthermore, it is newly discovered that the fusion between MxIRT1-vesicles and plasma membrane might play a key step response to iron.